The legal maxims of Islamic law (Excluding five leading legal maxims) and their applications in Islamic finance - Saiti, Buerhan; Abdullah, Adam (King Abdulaziz University Scientific Publishing Center, 2016)
Al-qawāʿid al-fiqhīyah or legal maxims of Islamic Law are the general rules of fiqh that portray the goals and objectives of the Sharīʿah. They are applied in various cases that come under the common rulings and play a very important role in deducing many rules of fiqh since they provide a guideline to come up with particular ḥukm. There are five leading maxims, as reflected in the Majallah, such as, al-umūr bi maqāṣidihā (matters are determined according to intentions), al-yaqīn la yazūl bi alshakk (certainty is not overruled by doubt), al-mashaqqah tajlib al-taysīr (hardship begets facility), al- ḍarar yuzāl (harm must be eliminated) and al-ʿādah muḥakkamah (custom is a basis for judgment). Other than these five leading maxims, which are applicable to a number of legal principles, there are other maxims, which are not as extensive as the main maxims, but nonetheless, address a number of more detailed issues in fiqh. Usually, the maxims incorporated in this category are either an extension of maxims derived from the five leading maxims or might be unrelated. This paper seeks to analyse those maxims, other than the leading maxims, which are related to Islamic finance and to understand their roles and applications in the Islamic banking and finance industry.